Traditional Games on Basic Movement Abilities of Elementary School Students - Ningsih, Yuni Fitriyah; Khusnul Khotimah; Sugeng, Imam; Suhartiningsih; ME Winarno; Safirah, Adita Dwi (LPPM Undiksha, 2024)
In elementary schools, physical education, sports, and health have experienced a decline in students' basic movement abilities, especially regarding running ability. This is in line with the increasing trend of inactive lifestyles among children, which has the potential to harm their physical health. This research aims to analyze the influence of traditional games on elementary school students' basic movement abilities. This research is a type of experimental research. This research uses a true experiment method with a Pre-test and Post-test Control Group Design. The research population was all class V students, totaling 42 students. Data was collected through interviews and tests. The instruments used in data collection were interview sheets and a 30-meter running test. The data analysis technique uses quantitative descriptive and independent sampling t-test differences. This research shows that integrating traditional games significantly affects students' basic movement abilities. Therefore, traditional games can effectively develop elementary school students' basic movement abilities. This research implies that schools should consider introducing traditional games in their curriculum to improve students' basic movement skills while preserving local culture.